Active case finding with case management: the key to tackling the COVID-19 pandemic. Issue 10243 (4th July 2020) - Li, Zhongjie; Chen, Qiulan; Feng, Luzhao; Rodewald, Lance; Xia, Yinyin; Yu, Hailiang; Zhang, Ruochen; An, Zhijie; Yin, Wenwu; Chen, Wei; Qin, Ying; Peng, Zhibin; et al.
Summary: COVID-19 was declared a pandemic by WHO on March 11, 2020, the first non-influenza pandemic, affecting more than 200 countries and areas, with more than 5·9 million cases by May 31, 2020. Countries have developed strategies to deal with the COVID-19 pandemic that fit their epidemiological situations, capacities, and values. We describe China's strategies for prevention and control of COVID-19 (containment and suppression) and their application, from the perspective of the COVID-19 experience to date in China. Although China has contained severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and nearly stopped indigenous transmission, a strong suppression effort must continue to prevent re-establishment of community transmission from importation-related cases. We believe that case finding and management, with identification and quarantine of close contacts, are vitally important containment measures and are essential in China's pathway forward. We describe the next steps planned in China that follow the containment effort. We believe that sharing countries' experiences will help the global community manage the COVID-19 pandemic by identifying what works in the struggle against SARS-CoV-2.